Implementasi Kurikulum Merdeka Dalam Meningkatkan Potensi Peserta Didik Di Sekolah Dasar - Christiananda, FR.; R, Suci Permata; Anggraini, Dewi; Maharani, Selvia; P, Nova Sugiana; Suwartini, Sri (CV. ITTC INDONESIA, 2024)
This research is motivated by the fact that the development of student potential can be addressed through educational activities at school. Education can be interpreted as a life process that aims to develop all the potential that exists in a person so that he can live and be able to appreciate it fully so that he becomes an educated individual, both cognitively, emotionally and psychologically. This research aims to determine the implementation of the independent curriculum in increasing the potential of students in elementary schools. The approach used is qualitative with descriptive methods. The research results show that learning objectives must help students have the ability to think critically and solve problems, create and innovate, have communication and collaboration skills and have character. This research uses qualitative methods with literature studies. Literature study is a series of activities relating to methods of collecting library data, reading and taking notes, as well as processing research materials (Zed, 2008, p.3).